Bicuspid Aortic Valve and Pregnancy - S. O. Siromakha; Iu. V. Davydova; V. I. Kravchenko (Український журнал серцево-судинної хірургії, 2021)
Bicuspid aortic valve (BAV) is the most common congenital heart disease. Severe stenosis of BAV and its combination with aortic pathology can cause significant adverse maternal and perinatal consequences. The optimal strategy for medical care of pregnant women with BAV has not been fully elucidated and requires further research. This paper presents 7.5 years of work experience of a multidisciplinary team of experts in obstetric cardiology and cardiac surgery in the medical care of pregnant women with BAV and co-existing pathology of the heart and aorta. The experience is based on modern international guidelines, our own research efforts and hospital protocols. Primary expert cardiac screening of 2,469 pregnant women revealed 4.3% of patients (n=106) with BAV. The choice of the strategy for their care was personalized and based on the degree of BAV lesions, any concomitant pathology of the heart and aorta, symptoms and life-threatening conditions. The article analyzes the experience of medical care of pregnant patients with BAV bearing high cardiovascular risk (n=24), presents indications for a certain type of medical care, method and place of birth before cardiac surgery during pregnancy. The types and optimal time for performing interventions during pregnancy and the postpartum period were discussed. Perinatal losses (n=3) were analyzed. The chosen strategy is effective, as evidenced by the absence of negative maternal consequences in the immediate and long-term follow-up period.